Antineoplastic drugs contamination of workplace surfaces in two Portuguese hospitals - Viegas, Susana (2014)
Despite the classification as known or suspected human carcinogens, by the International Agency for Research on Cancer, the antineoplastic drugs are extensively used in cancer treatment due to their specificity and efficacy. As human carcinogens, these drugs represent a serious threat to the healthcare workers involved in their preparation and administration. This work aims to contribute to better characterize the occupational exposure of healthcare professionals to antineoplastic drugs, by assessing workplace surfaces contamination of pharmacy and administration units of two Portuguese hospitals. Surface contamination was assessed by the determination of cyclophosphamide, 5-fluorouracil, and paclitaxel. These three drugs were used as surrogate markers for surfaces contamination by cytotoxic drugs. Wipe samples were taken and analyzed by HPLCDAD. From the total of 327 analyzed samples, in 121 (37%) was possible to detect and quantify at least one drug. Additionally, 28 samples (8.6 %) indicate contamination by more than one antineoplastic drug, mainly in the administration unit, in both hospitals. Considering the findings in both hospitals, specific measures should be taken, particularly those related with the promotion of good practices and safety procedures and also routine monitoring of surfaces contamination in order to guarantee the appliance of safety measures.